Web Services Assurance for Insurance emerging test automation solutions are key to a successful web services strategy. - Hayes, Linda
Timely delivery of a quality Web services solution requires functional testing at each layer, throughout the development process. New test automation solutions empower insurance domain experts to verify critical business processes at each phase and layer of delivery.